Pengaruh Self-Assessment System Terhadap Penerimaan Pajak Penghasilan Pasal 25 Wajib Pajak Orang Pribadi Pada Salah Satu Kantor Pelayanan Pajak Di Kota Bandung - Rina Eytha Farida; Anton Tirta Komara; Jimmy Rusjiana; Lungguh Jatmika (Center of Research, STIE Pasundan, Bandung, Indonesia., 2022)
The purpose of this study was to determine and test the relationship and extent of the influence of the Self Assessment System variable on Income Tax Article 25 Receipts of Individuals in one of the Primary Tax Service Offices in Bandung.The research method used is descriptive and verification research methods. Where research aims to analyze data by describing or describing the data that collect as it is without intending to make conclusions that apply to the public. The second method is the verification method, where research is used to test the truth of a hypothesis which is carried out through data collection in the field. In an effort to obtain data and information that will support this research, namely by collecting secondary data.Based on the research results, the correlation coefficient is 0.757 or 75.7%, meaning that there is a strong relationship between the variable (X) Self Assessment System and variable (Y) Income Tax Article 25 income for individuals. The results of the study show the results of a simple linear regression, namely the equation Y = 18.324 + 0.423x, this shows that the Self Assessment System has a positive effect on income tax article 25 for individuals. The results of the calculation of the significant test (t test) with a significant level of 0.05 obtained tcount greater than ttable (5.436 > 1.717), this means that H0 is rejected and Ha is accepted. Thus proving that there is a significant influence between the Self Assessment System on the receipt of Income Tax Article 25 for individuals. The magnitude of the influence of the Self Assessment System on the receipt of Income Tax Article 25 for individuals is shown from the calculation of the coefficient of determination which is 57.3%, while the remaining 42.7% is the influence of other factors or variables not examined by the author.